Optimal fixed charge–rate coordination of plug-in electric vehicle incorporating capacitor and OLTC switching to minimize power loss and voltage deviation - Rahman, Mir Toufikur; Othman, Mohamadariff; Mokhlis, Hazlie; Muhammad, Munir Zuhdin; Bouchekara, Houssem (Institute of Electrical Engineers of Japan, 2018)
Integration of plug-in electric vehicles (PEVs) in a smart grid largely deteriorates the performances of the system. This paper proposes a two-stage optimization approach to optimize customer satisfaction as well as grid performances when fixed charge–rate PEV coordination, switching capacitor and on-load tap charger (OLTC) are coordinated simultaneously. To coordinate PEV charging, capacitor and OLTC, an efficient binary particle swarm optimization (BPSO) has been applied. The main consideration in this optimal coordination is to minimize the daily power loss and voltage deviation while maximizing customer satisfaction. Simulation results are compared with the variable charge–rate coordination that is proposed previously.